The Effectiveness of The Argument-Driven Inquiry (ADI) Model in Enhancing Critical Thinking Skills: A Literature Review - Nurmala Mustofa; Naya Mahdiyya Sari; Rizka Isnaeni; Nasywa Dwi Kamila (Indonesian Journal of STEM Education, 2026)
This research aims to analyze the effectiveness of the Argument-Driven Inquiry (ADI) learning model in improving students' critical thinking skills through a literature study approach. The method used is a literature review of 10 relevant scientific articles published in the period 2017–2026. Data were analyzed descriptively by identifying main findings related to the effectiveness of the ADI model, indicators of increased critical thinking, as well as factors that influence the success of its implementation. The results of the study show that the ADI model consistently has a positive influence on improving critical thinking skills at various levels of education, from elementary school to college. The most dominant increase occurred in the analysis, evaluation, inference and argumentation indicators. Apart from that, the effectiveness of the ADI model is influenced by academic abilities, student learning styles, the teacher's role as a facilitator, and the use of interactive learning media. The ADI model has also proven to be flexible because it can be applied to various subjects, not only in the field of science but also in language learning. Thus, the ADI model can be an effective innovative learning alternative in developing students' Higher Order Thinking Skills.